Curriculum perspectives and development - Bachmeier, Alexander (Education in a competitive and globalizing world series., 2020)
"Curriculum Perspectives and Development considers how the school curriculum should be organised in terms of subjects, considering the relative merits of seeking to integrate different traditional areas of knowledge rather than organising the curriculum to reflect disciplinary structures. The authors propose an extended Kantian model of arts education, presenting its verification through a survey of the Hong Kong arts education curriculum as a case study. In order to maximize growth and facilitate evaluation, it is suggested that students strive to demonstrate higher-level reflective writing. As such, this compilation describes the portfolio-based evaluation system one program employs. Lastly, the authors explore the relationship between spirituality and transformational learning, examining what spirituality may look like in a classroom setting and how it may potentially facilitate transformational learning"--